2020
DOI: 10.1038/s41416-020-01138-3
|View full text |Cite
|
Sign up to set email alerts
|

Trastuzumab upregulates programmed death ligand-1 expression through interaction with NK cells in gastric cancer

Abstract: Background The predictive significance of programmed death ligand 1 (PD-L1) for programmed death 1 (PD-1) inhibitors remains unclear in gastric cancer (GC) due to the dynamic alteration by treatments. We aimed to elucidate the effects of trastuzumab (Tmab) on PD-L1 expression in GC. Methods PD-L1 expression was evaluated by multicolour flow cytometry analysis after co-culturing GG cell lines and immune cells with Tmab. IFN-γ in the co-culture exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…PD-1 is an immune checkpoint molecule that is expressed on several types of immune cells, including effector T cells. It induces exhaustion of the effector function by engaging its ligand PD-L1 [ 30 ]. Several studies have reported the status of PD-1 or PD-L1 in gastric cancer, and PD-1 or PD-L1 has been shown to be potential predictive biomarker for recurrence and prognosis for gastric cancer in certain settings [ 31 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…PD-1 is an immune checkpoint molecule that is expressed on several types of immune cells, including effector T cells. It induces exhaustion of the effector function by engaging its ligand PD-L1 [ 30 ]. Several studies have reported the status of PD-1 or PD-L1 in gastric cancer, and PD-1 or PD-L1 has been shown to be potential predictive biomarker for recurrence and prognosis for gastric cancer in certain settings [ 31 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…PD-L1 suppresses immune effectors through the ligation of PD-1 [ 208 ]. Both NK cells and T cells are important sources of IFN-γ that could stimulate tumor PD-L1 expression [ 209 ]. However, whether PD-L1 has a major role is suppressing trastuzumab-induced immunity and clinical activity is not clear from clinic studies.…”
Section: Molecular and Cellular Mechanisms Of Resistance To Trastuzumabmentioning
confidence: 99%
“…Trastuzumab’s capacity in upregulating PD-L1 expression, by the recruitment of IFNgamma-secreting immune effector cells, has been shown as a mechanism of resistance to trastuzumab [ 63 ]. Furthermore, the mAbs that are bound to tumor cells engage innate immune effector cells via their Fc receptor, resulting in ADCC [ 64 , 65 ], which in turn also results in the upregulation of PD-L1 [ 66 ]. It has been shown that the increased ability of tumor cells to evade the immune system is attributed to their PD-L1 expression capacity, allowing their interaction with PD-1-expressing immune cells [ 67 ].…”
Section: Combination Of Her-2/neu-targeted Therapy With Immune Checkp...mentioning
confidence: 99%